PENGARUH PENERAPAN FINTECH DAN INKLUSI KEUANGAN TERHADAP KEBERLANJUTAN UMKM KOTA BENGKULU - Ana Nur Lestari; Desi Fitria; Rina yuniarti; Dinal Eka Pertiwi (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the impact of financial technology (fintech) implementation and financial inclusion on the sustainability of micro, small, and medium enterprises (MSMEs) in Bengkulu City. The research method used a quantitative approach, with primary data obtained through questionnaires distributed to 75 MSMEs operating in the culinary sector in Bengkulu City. The data analysis technique used multiple linear regression with the help of SPSS. The results indicate that partially, fintech implementation has no significant effect on MSME sustainability, while financial inclusion has a positive and significant effect on MSME sustainability. Simultaneously, fintech implementation and financial inclusion have a significant effect on MSME sustainability. The conclusion of this study indicates that financial inclusion plays a crucial role in supporting MSME sustainability, while fintech implementation has not yet significantly impacted MSME business sustainability in Bengkulu City. Keywords: Fintech, Financial Inclusion, MSME Sustainability, Msmes